Impact of Corporate Governance on Accounting Irregularities in Vietnamese Listed Companies: The Moderating Role of Financial Leverage - Thuy Ho; Tai Vu; Thao Nguyen; Ngoc Huynh (Asian Academy of Management Journal of Accounting and Finance, 2025)
This study aims to address limitations of previous research by testing the moderating role of financial leverage on the relationship between corporate governance (CG) and accounting irregularities (AIs). We employ both logistic regression and two-step system Generalised Method of Moments (GMM) regression to test these relationships through panel data of 382 companies listed on the Vietnamese stock market from 2011 to 2022. While a larger board of directors (BOD) size or companies being audited by Big 4 companies may reduce the likelihood of AIs, a chief executive officer (CEO) who also holds the position of chairman of the BOD or a longer audit tenure can increase the chance of AIs. Notably, the moderating role of financial leverage has a significant influence on the relationship between CG mechanisms and the likelihood of AIs. This study’s findings provide policymakers and other stakeholders a strong foundation for making choices about building better CG practices, ultimately reducing the likelihood of AIs. Importantly, this research is the first to explore how financial leverage moderates the relationship between CG and AIs.